Probabilistic and statistical methods for designing and analyzing limit states/Tikimybinis ir statistinis ribinų būvių projektavimo ir analizės metodai - Užpolevičius, Benediktas (Journal of Civil Engineering and Management, 2001)
Errors of partial reliability factor (PRF) method, being used in operating codes to provide required reliability of construction work (foundations, structures and their systems), are discussed. It is pointed out that additional resistance (strength, stiffness, etc) of the members to compensate these errors is required, and it makes much more than 10%. The main cause of these shortcomings is that in the PRF method, for the sake of simplicity, independent partial coefficients and limited number of these coefficients are applied. Direct probabilistic and statistical methods (without application of partial coefficients and design values) are proposed. It is demonstrated that these methods are free of systematic errors which are characteristic of the known codified (standardized) probability calculations. The proposed methods make up a unified method used for foundations and structures, uniformly based on theoretical conclusions of probability theory and mathematical statistics. These economy seeking methods are intended for effective use (without change of codes) of available additional information, which is made of different amount of data of statistical measurements or statistical observations on minimal values of soils and building material mechanical characteristics of structures and maximum values of loads, actions and their combinations during the operation period, geometrical dimensions of critical cross-sections, errors of algorithms for calculation of resistance and action effects, control errors made by people during design, construction, operation of construction works, etc. In case of a limited amount of information the proposed statistical model is to be used. In addition, the proposed method is adjusted for effective use of the known reliability solutions of economical and social optimisation (in relation to economical and social damage caused by the limit state, human safety and other factors) co-ordinating them with application experience of PRF code method and statistical multidimensional data of limit state frequency. Areas of application and economy of the proposed probabilistic and statistical methods are presented in Table 1. National and established specifications prepared for probabilistic and statistical calculation design and tests of foundations, structures and their systems are discussed. Practical application and economical comparison of calculation of construction members by PRF, probabilistic and statistical methods (area of the cross-section, foundation pad base A% in relation to that determined by SNiP codes).Article in Lithuanian.First Published Online: 30 Jul 2012